PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN MILENIAL DOMESTIK KE TAMANSARI, YOGYAKARTA - Setiyaningsih, Suci; Agus Wikanatha Sagita, Putu; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
Electronic Word of Mouth (EWOM) is the communication media which can help shares the information there are consumer reviews of product or services, one of EWOM’s communication media is Instagram. Through Instagram tourists can find out the spread of information through reviews, comments, caption and hastags that indirectly provide benefit for potensial tourists in making decision to visit a tourist destination. The purpose of this research is to determine the influence of Electronic Word of Mouth (EWOM) on Instagram of the domestic milennial tourists visiting decisions to Tamansari Yogyakarta. This study use accidental sampling to determinant the sample. The data collected by interview, observation,  shares the questionnaries from google form, literature review,  documentations and netnography. The data analysis used simple linear regression analysis which had previously had been analyzed by classical assumptions. The result of this study the significance of the EWOM variable 0,01 < 0,05 and the t count was 12,808 > t table 1,981. The result of determination R Square is 60,03%. Based on this result, partially and simultaneously the Electronic Word of Mouth (EWOM) on Instagram has a positive and significant influence on the domestic millennial tourist visiting decisions to Tamansari Yogyakarta.